The best way to assess oedema using T1, T2 mapping or three-dimensional T2-weighted fast-spin-echo triple inversion recovery sequences via cardiovascular MRI in outpatients with suspected myocarditis - Jeserich, M.; Kimmel, S.; Maisch, P.; von Rauffer, S.; Achenbach, Stephan (Clinical Radiology, 2020)
AIM: To evaluated T1-, T2 mapping, and a three-dimensional (3D) T2-weighted fast-spin-echo triple inversion recovery sequences (3D STIR) for diagnosing myocardial oedema in patients with suspected early myocarditis and at follow-up. MATERIALS AND METHODS: Sixteen patients with suspected myocarditis and 15 controls matched for gender and age were examined prospectively. To evaluate oedema, an electrocardiogram-triggered T1 and T2 mapping with a gradient spin echo technique and 3D STIR sequences were used to cover the entire left ventricle. The signal intensity ratio (heart muscle in relation to skeletal muscle) was calculated (3D STIR ratio). All patients underwent repeat examinations at follow-up. RESULTS: The mean 3D-STIR ratio was 2.14±0.45 at the patients' initial examination as compared to the control patients' 1.54±0.18 in (p=0.0001) and 1.75±0.16 in patients at follow-up (p=0.002 versus first visit). The 3D STIR ratio of the septum, anterior, lateral, and inferior wall also differed significantly between patients and controls. No significant difference was observed in T1 and T2 mapping between patients and controls at baseline and patients at follow-up. CONCLUSIONS: A significantly higher global signal intensity ratio with 3D-STIR was identified in patients with suspected myocarditis compared to controls, and a significant change during follow-up. No significant difference was detected in T1-, T2 mapping between patients and controls, or between the initial examination and follow-up of patients. The global 3D-STIR ratio may therefore be useful for the diagnosis of myocarditis and should be explored further.
CRIS-Team Scopus Importer:2020-03-10